A Case for Mezirow’s Transformative Learning - Rieswan Pangawira Kurnia (Diligentia: Journal of Theology and Christian Education, 2021)
Jack Mezirow’s transformative learning theory is one of the most referenced adult education theories. In his theories, transformative learning is the process of effecting change in a frame of reference, using structures of assumption to understand our experiences. Transformative learners move toward a frame of reference with more inclusive self-reflection and more integration of experience. Adult educators should help students become aware and critical of assumptions, their own, and others’. As adult learners, we should be part of transformative learning by being critical with our frames of reference, starting from understanding the world unconsciously in childhood experience, and moving toward a frame of reference with more self-reflection and integration of experience. We should understand the forms, autonomous thinking in transformation theory, and the two domains of learning—instrumental and communicative—as well as their definitions, comparisons, and applications in adult learning. Our experience’s premises, distortions, and situations should be identified and analysed through a transformative lens. Our meaning perspectives are broadened as they are challenged through many deformations and reformations.